Spatiotemporal variations and source identification of atmospheric nitrated and oxygenated polycyclic aromatic hydrocarbons in the coastal cities of the Bohai and Yellow Seas in northern China. (September 2021) - Chen, LiYuan; Liu, WeiJian; Tao, Shu; Liu, WenXin
Abstract: Gaseous and particulate nitrated polycyclic aromatic hydrocarbons (NPAHs, 12 species) and oxygenated polycyclic aromatic hydrocarbons (OPAHs, 4 species) in seven coastal cities of the Bohai and Yellow Seas were determined throughout the year. The annual arithmetical mean concentrations of ΣNPAH12 and ΣOPAH4 were 737 ± 475 pg/m 3 and 35.3 ± 26.8 ng/m 3 . NPAHs and OPAHs existed mainly in the gaseous phase, accounted for 88.5% and 95.2% of the total concentrations. Air concentrations of ΣNPAH12 and ΣOPAH4 in the coastal cities of the Yellow Sea were significantly lower ( p  < 0.05) than those of the Bohai Sea. Air concentrations of ΣNPAH12 and ΣOPAH4 were significantly higher ( p  < 0.01) in winter than in summer. Strong secondary formation of atmospheric NPAHs and OPAHs occurred in all of the studied cities. The sequence of annual contribution of the emission sources of airborne NPAHs determined by positive matrix factorization was traffic exhaust > combustion of solid fuels (coal and biomass) > secondary formation, while for OPAHs, it was combustion of solid fuels > secondary formation > traffic exhaust. The combustion of solid fuels served as the main source of NPAHs and OPAHs in winter, while secondary formation was the predominant source in summer. Interregional transport may exert an important effect on the local atmospheric NPAHs and OPAHs by potential source contribution function analysis. The estimated incremental lifetime cancer risk ( ILCR ) due to inhalation exposure to specific NPAHs ranged from 2.9 × 10 −12 to 6.2 × 10 −6 (median at 4.8 × 10 −9 ) was mainly attributed to exposure before the age of 16. Graphical abstract: Image 1 Highlights: NPAHs and OPAHs were monitored in seven coastal cities in Northern China for one year. Significant increases in the levels of NPAHs and OPAHs occurred in winter. Coal combustion and biomass burning served as the main sources in winter. Secondary sources contributed considerably to NPAHs and OPAHs, especially in summer. Regional inputs contributed to the local concentrations of NPAHs and OPAHs. Abstract : Higher concentrations of NPAHs and OPAHs occurred in winter, partitioning predominantly existed in the gaseous phase, and the main sources were the combustion of coal and biomass, followed by traffic exhaust and secondary formation.